Global research progress of nanomedicine and colorectal cancer: a bibliometrics and visualization analysis - Tian, Siyu; Chen, Min (Frontiers in Oncology, 2024)
BackgroundSurgery and chemoradiotherapy are the main clinical treatment methods for colorectal cancer (CRC), but the prognosis is poor. The emergence of nanomedicine brings bright light to the treatment of CRC. However, there has not been a comprehensive and systematic analysis of CRC and nanomedicine by bibliometrics.MethodsWe searched the Web of Science Core Collection database (WOSCC) for relevant literature published from 2011 to 2024. We used VOSviewer and Citespace to analyze countries, institutions, authors, keywords, highly cited references, and co-cited references.Results3105 pieces of literatures were included in the research analysis, and PEOPLES R CHINA and the USA took the leading position in the number of papers published and had academic influence. The Chinese Academy of Sciences posted the most papers. The most prolific scholar was Abnous Khalil. The level of economic development is inversely proportional to the number of cases and deaths of colorectal cancer. Nanoparticles (NPs), the nanomedical drug delivery system (NDDS) is a hot topic in the field. Photodynamic therapy (PDT), immunogenic cell death (ICD), tumor microenvironment (TEM), folic acid, and pH are the cutting edge of the field.ConclusionThis paper introduces the research hotspot, emphasis, and frontier of CRC and nanomedicine, and points out the direction for this field.